UTILITY OF DIFFERENT TYPES OF SIVANA KARMA IN UTKARTANA – A COMPARATIVE STUDY (AYUSHDHARA, 2016)
Episiotomy (Utkartana) is a surgical incision on the perineum and the posterior vaginal wall during the second stage of labour, for the purpose of either aiding the actual delivery process or preventing tears and lacerations, it is the most common surgical operations performed in obstetrics. Repair of episiotomy is also an important aspect. If it is not repaired properly it may leads to complications like wound dehiscence, rectovaginal fistula, dyspareunia. While explaining the concept of Mudhagarbha chikitsaacharyas have mentioned Utkartana vidhi to expel the Mudhagarbha which can be correlated to episiotomy procedure where Acharya mentioned that cutting of organ which is obstructing is Utkartana karma. Once the process of delivery completes the next immediate measure to be followed is suturing the cut part i.e., Seevana karma. In Ashtavidhashastra karma Adyaya, Acharya Sushruta has told 8 different types of Shastra karma`s, Sivana karma is one among them. And Sivana is also told as best treatment in Bhinna, Medhasamuttha vrana & Sadyovrana. Perineal region can be considered as Medhosamutthita and Utkartana as Vaidyakrutasadyovrana, so Sivana karma can be considered as best treatment for Utkartana. The contemporary science explains detailed description about repair of episiotomy in 3 layers with different type of suturing technique. Here by we have made an attempt to study efficacy of different types of Sivana karma done in 3 groups i.e., skin suturing done with Subcutaneous suturing, Matters suturing, Continuous suturing and also to evaluate the faster and easy wound healing without complication.